Gravity relationship and trade : is distance becoming less important with advances in modern technologies? - Hejnová, Aneta (2018)
The gravity model is an abundantly used method when estimating bilateral trade flows. Apart from other approaches, the gravity model is able to take into account the distance between the two trading partners as well as their size. Last decades have brought to us many new technological advances. One of them is the internet and the possibility to sell things online. That possibility has created a new job field – digital marketing, which is now the key determinant of the success of the e-commerce companies. Can these new advances partially compensate for the negative effect of distance? Moreover, what are the key variables determining the success of the company? We are working with panel data from 28 countries of the European Union (EU) in period 2010-2017. Using the panel data analysis, we aim to attempt to construct a gravity model of the international bilateral trade in printed matters among the Czech Republic (CZ) and other selected EU countries, which is subsequently compared on a real-life example thanks to the internal data from the Europosters company. We are able to create a data analysis, future marketing strategy and financial suggestions for each market, based on the data reviewed with OLS and random and fixed effects tests.